Winning Back the Intellectuals: Inside Canada’s “First War on Terror,” 1968-1970 - Gauvreau, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
AbstractHistorical treatments of the October Crisis have tended to focus on a simple dichotomy between the aims of the Canadian government and the Front de Libération du Québec, have suggested the tensions in the relationship between federal and provincial levels of government during the crisis, or have sought to situate the FLQ within the emergence of a new strain of radical ideas in Québec during the 1960s. This paper takes as its starting-point the irony of the reluctance of the Trudeau government to brand the FLQ as “terrorists,” and examines the federal government’s response within a larger strategy to force the intellectual communities in both English Canada and Québec away from a sympathy for student radicalism and international decolonization struggles. It situates the Trudeau government’s “war on terror” as less an episodic response to the kidnappings of James Cross and Pierre Laporte, but within a growing strand of conservatism in the encounter of the authorities with elements of the cultural revolution of the 1960s. It poses the question of whether the nature of the federal government’s response may have been due to the desire, among members of Prime Minister Pierre Trudeau’s inner circle, to promote a new type of liberal ideology that sought to dispense with older versions that legitimated civic participation through non-elected, “representative” bodies by defining the latter as conscious or unwitting accomplices of terrorist violence. The paper is based on a range of newly-declassified documents from both the federal cabinet and the security services deposited in Pierre Trudeau’s prime ministerial archive, as well as a new reading of newspaper and media sources in Québec.